NIM-R7, a novel marker for resting B1 and marginal-zone B lymphocytes, is also expressed on activated T and B cells - Manjarrez-Orduño, Nataly (Blackwell Publishing Inc, 2003)
In mice, follicular B cells have been studied in detail, while two other B-cell subpopulations – marginal-zone B and B1 cells – are less well understood. In this work we report the expression pattern of p58, a lymphocyte-activation marker, recognized by rat monoclonal antibody, NIM-R7, and present on the latter two cell subpopulations. Staining with NIM-R7 showed that undisturbed marginal-zone B cells, as well as peritoneal cavity and splenic B1a cells, constitutively expressed p58, whereas follicular B cells and resting T lymphocytes did not. Ontogenic analysis of different compartments showed that p58 did not appear at any stage of development, prior to the development of mature T or B2 lymphocytes. Upon polyclonal stimulation, however, p58 appeared on both T and B2 lymphocytes. Finally, ricin A-conjugated NIM-R7 was able to kill the BCL1 lymphoma without effect on mature resting B2 cells. Therefore, p58 may be a potential target for diagnosis or therapy of B1 and marginal-zone B-cell malignancies.